PENGARUH ECOENZYM DAN SP-36 TERHADAP BEBERAPA SIFAT KIMIA TANAH DAN PERTUMBUHAN TANAMAN SAWI (Brassica juncea L.) PADA ULTISOL: Effect of Ecoenzyme and SP-36 on Some soil properties and Growth of Mustard (Brassica juncea L.) Planted on an Ultisol - S.N. Lumbanraja; Dedik Budianta; A.M. Rohim (AgriPeat, 2022)
This experiment was conducted in a Greenhouse of Soil Science Department from March to May 2021. Soil properties analysis was carried out at the Laboratory of Chemistry, Biology and Soil Fertility of Soil Science Department, Faculty of Agriculture, Sriwijaya University. This experiment aims to study the effect of ecoenzym and SP-36 application on pH and P availability and growth of Mustard planted on Ultisol. This experiment was designed using the Completely Randomized Design consisting of 8 treatments which were B0: Control, B1: 10 ml L-1 ecoenzyme (EE), B2: 5 ton ha-1 of EE solid waste, B3: 50% recommended dose of 56.25 kg SP-36 ha-1, B4: 100% recommended dose of 112.5 kg SP-36 ha-1, B5: 10 ml L-1 EE + 5 ton ha-1 EE solid waste, B6: 50% recommended dose of 56.25 kg SP-36 ha-1 + 10 ml L-1 EE + 5 ton ha-1 EE solid waste, B7: 100% recommended dose of 112.5 kg SP-36 ha-1 + 10 ml L-1 EE + 5 ton ha-1 of EE solid waste. The treatment was replicated 3 times thus the total of experiment were 24 units. Variables observed were soil pH and P availability, growth and yield of Mustard. The results showed that the treatments of ecoenzyme and ecoenzyme solid waste and SP-36 fertilizer had significant effects on the soil pH, P-Availability, plant height, leaves number, root length, wet and dry weight of mustard. The B4 treatment with SP-36 treatment dose of 112.5 kg ha-1 resulted the best effect on soil pH and soil P-Availability, growth and yield of mustard